Pengenalan Kosa Kata Baru Dalam Bahasa Inggris dan Bahasa Indonesia Selama Masa Pandemi Covid-19 - Fauziah Nur; Tiurmaya Agustina; Rita Napitulu (CV. Ulil Albab Corp, 2023)
This community service activity aims to introduce and teach new vocabulary in English and Indonesian that emerged during the Covid-19 pandemic. The emergence of new vocabulary in English and Indonesian has a positive impact on language development for both languages. This activity was carried out at the Islamic Elementary School Nurul Yaqin Burhaniah which is located at Jalan Limau Mungkur, Desa Dagang Kerawan, Deli Serdang. Participants consisted of 30 grade IV elementary school students. The method used is the theory of practice. The results obtained after carrying out this activity are knowledge and skills in using new vocabulary during the Covid-19 pandemic and increasing students' knowledge about the importance of maintaining cleanliness and health in order to avoid the adverse effects of the Covid-19 pandemic. This activity received a good response and with positive results as well. However, activities like this can be carried out simultaneously to get even better results.